La complessità della relazione medico-paziente in nefrologia: perché è ancora più importante occuparsene oggi? - Marilena Cara (AboutScience Srl, 2022)
Medicine is more than just a science: it is a human contact between men. We must not forget that "Psyche depends on the body and the body depends on the psyche". The 21st Century man's Psyche is more stressed than in the past, as we live in a complexity increasingly understood with the passage of time. The only way to take care of the sick person in the body, and therefore suffering in the psyche, can only be that which rests on the relationship, since the relationship, in my opinion, can be considered the bridge between the psyche and the soma. If the medical technique today does not pass through the relationship could it be effective in the cure? Trust in the doctor today is no longer a certainty, as medicine has lost its character of sacredness, but must be acquired and conquered through a dedicated and continuous relationship. Unlike other pathologies, nephrology does not end in a diagnosis or in a therapy that is provided at home, but the patient's only point of reference is the nephrology nursing staff. Effective communication will lead to a reduction in the time taken for communication, improving the patient's ability to understand and trust, reducing the operator's effort and improving the therapeutic result. Today's medicine, and today's "healers" can no longer fail to deal with the management of the operator-patient relationship in order to meet the demands that today's society and healthcare organization make in the medical field.